Combinations of structures - S.V. Sudoplatov (Известия Иркутского государственного университета: Серия "Математика", 2018)
We investigate combinations of structures by families of structures relative to families of unary predicates and equivalence relations. Conditions preserving $ω$-categoricity and Ehrenfeuchtness under these combinations are characterized. The notions of e-spectra are introduced and possibilities for e-spectra are described.